Atomic Scaled Depth Correlation to the Oxygen Reduction Reaction Performance of Single Atom Ni Alloy to the NiO2 Supported Pd Nanocrystal. Issue 11 (8th February 2023) - Li, Haolin; Dai, Sheng; Wu, Yawei; Dong, Qi; Chen, Jianjun; Chen, Hsin‐Yi Tiffany; Hu, Alice; Chou, Jyh‐Pin; Chen, Tsan‐Yao
Abstract: This study demonstrates the intercalation of single‐atom Ni (Ni SA ) substantially reduces the reaction activity of Ni oxide supported Pd nanoparticle (NiO2 /Pd) in the oxygen reduction reaction (ORR). The results indicate the transition states kinetically consolidate the adsorption energy for the chemisorbed O and OH species on the ORR activity. Notably, the NiO2 /Ni 1 /Pd performs the optimum ORR behavior with the lowest barrier of 0.49 eV and moderate second‐step barrier of 0.30 eV consequently confirming its utmost ORR performance. Through the stepwise cross‐level demonstrations, a structure– E ads –Δ E correspondence for the proposed NiO2 /Ni n /Pd systems is established. Most importantly, such a correspondence reveals that the electronic structure of heterogeneous catalysts can be significantly differed by the segregation of atomic clusters in different dimensions and locations. Besides, the doping‐depth effect exploration of the Ni SA in the NiO2 /Pd structure intrinsically elucidates that the Ni atom doping in the subsurface induces the most fruitful Ni SA /Pd ML synergy combining the electronic and strain effects to optimize the ORR, whereas this desired synergy diminishes at high Pd coverages. Overall, the results not only rationalize the variation in the redox properties but most importantly provides a precision evaluation of the process window for optimizing the configuration and composition of bimetallic catalysts in practical experiments. Abstract : A diagram illustrating how charge transfer occurs between NiO2, interfacial Ni atoms, outer Pd‐shell atoms, and the surface species involved in the oxygen reduction reaction in the NiO2 /Ni1 /Pd system. Using small amounts of inexpensive nickel at the interface with costly subsurface‐Pd layer creates a unique local synergy, leading to improved reactivity and selectivity in the catalysts.